The Interaction of Digital Lifestyle and Food Waste on Household Food Security among Urban Millennials: Evidence from Palembang City, Indonesia - Yuli Nurhayati; Eri Triharyati (Universitas Bangka Belitung, 2025)
Household food security in urban areas, especially among millennials, is becoming an increasingly important issue as lifestyles and consumption patterns change due to the digitization of food services. This study aims to analyze the level of food security among millennial households in Palembang and examine the effect of spending on food delivery and food waste on the Household Food Insecurity Access Scale (HFIAS) score. Data were obtained from millennial household respondents through a questionnaire survey, with the HFIAS score as the dependent variable. The analysis was conducted using Ordinary Least Squares (OLS) regression, followed by Poisson regression as an alternative model suitable for count data. The results showed that the average HFIAS score was 3.17, with the majority (87%) of households falling into the mildly food insecure category. OLS and Poisson regressions show that spending on food delivery and food waste has a negative effect on food security. This study concludes that the food security of millennial households in Palembang is relatively vulnerable, mainly due to their increasing dependence on food delivery services.